Colchicine for the Treatment of Cardiac Injury in Hospitalized Patients With Coronavirus Disease-19 - Amir Rabbani; Asim Rafique; Xiaoyan Wang; Danielle Campbell; Daniel Wang; Nicholas Brownell; Kenia Capdevilla; Victoria Garabedian; Sandra Chaparro; Raul Herrera; Rushi V. Parikh; Reza Ardehali (Frontiers in Cardiovascular Medicine, 2022)
IntroductionThe impact of colchicine on hospitalized patients with Coronavirus disease-19 (COVID-19) related cardiac injury is unknown.Materials and MethodsIn this multicenter randomized controlled open-label clinical trial, we randomized hospitalized adult patients with documented COVID-19 and evidence of cardiac injury in a 1:1 ratio to either colchicine 0.6 mg po twice daily for 30 days plus standard of care or standard of care alone. Cardiac injury was defined as elevated cardiac biomarkers, new arrhythmia, new/worsened left ventricular dysfunction, or new pericardial effusion. The primary endpoint was the composite of all-cause mortality, need for mechanical ventilation, or need for mechanical circulatory support (MCS) at 90 days. Key secondary endpoints included the individual components of the primary endpoint and change in and at least 2-grade reduction in the World Health Organization (WHO) Ordinal Scale at 30 days. The trial is registered with clinicaltrials.gov (NCT04355143).ResultsWe enrolled 93 patients, 48 patients in the colchicine arm and 45 in the control arm. There was no significant difference in the primary outcome between the colchicine and control arms (19 vs. 15%, p = 0.78), nor in the individual components of all-cause mortality (17 vs. 15%, p = 1.0) and need for mechanical ventilation (8 vs. 5%, p = 0.68); no patients in either group required MCS. The change in (−1.8 ± 2.4 vs. −1.2 ± 2.0, p = 0.12) and at least 2-grade reduction (75 vs. 75%, p = 1.0) in the WHO ordinal scale was also similar between groups.ConclusionPatients hospitalized with COVID-19 and evidence of cardiac injury did not benefit from colchicine therapy.